Split second - Coulter, Catherine (New York : G.P. Putnam's Sons, 2011)
"A serial killer is on the loose, and it's up to FBI agents Dillon Savich and Lacey Sherlock to bring him down. They soon discover that the killer has blood ties to the infamous and now long-dead monster Ted Bundy. Savich and Sherlock are joined by agents Lucy Carlyle and Cooper McKnight, and the chase is on..." -- Jkt. flap.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Savich, Dillon (Fictitious character) -- Fiction; Sherlock, Lacey (Fictitious character) -- Fiction; Serial murderers -- Fiction; Murder -- Investigation -- Fiction; Suspense fiction